Assessing Guest Knowledge and Awareness of Sustainable Practices in 5- Star Hotels: A Comprehensive Study (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: The hospitality industry’s commitment to sustainability relies not only on implementation but also on  guest awareness and engagement. This study evaluates the degree of guest knowledge about sustainable hotel practices  and identifies which practices are most and least recognized. It further explores the sources through which guests  learn about these initiatives and examines the correlation between their awareness and willingness to support such  efforts. Objectives: The study aimed to assess guests’ awareness of sustainable practices, determine the most and least  known initiatives, identify key information sources, and analyse the relationship between knowledge and willingness to  engage in sustainability. Methodology: A descriptive research design was employed using a structured questionnaire  distributed via convenience sampling. Responses were collected from 385 hotel guests across India. Data analysis  through SPSS included descriptive statistics, one-sample t-tests, and Spearman’s rho correlation. Results: Recycling  and waste management programs (mean=3.92) and the use of eco-friendly toiletries (mean=3.80) were the most  recognized practices, while energy-efficient HVAC systems (mean=3.35), sewage treatment plants (mean=3.45), and  towel reuse programs (mean=3.34) were least known. All practices showed statistically significant mean scores above  the hypothesized moderate level of 3 (p < 0.001). Social media emerged as the most common information source, followed  by hotel websites and in-room materials. However, 17.9% of respondents reported no awareness of any practices, and  staff communication was the least reported source. A positive and statistically significant correlation (ρ=0.499, p
Keywords: Guest knowledge; sustainable practices; hotel sustainability; guest awareness; environmental sustainability; hospitality industry; correlation analysis